MET Exon 14 Alterations in Lung Cancer: Exon Skipping Extends Half-Life - Drilon, Alexander (Clin Cancer Res, 2016)
MET exon 14 alterations are a diverse group of mutations, many of which disrupt splice acceptor or donor sites leading to exon 14 skipping, impaired receptor degradation, and oncogenic transformation. These alterations are clinically targetable with MET-directed therapy.